A superiority–inferiority hypothesis on disparagement humor: The role of disposition toward ridicule - Hatzithomas, Leonidas; Voutsa, Maria C.; Boutsouki, Christina; Zotos, Yorgos (My University, 2021)
The present paper adopts and substantiates a superiority–inferiority hypothesis on disparagement humor generation and appreciation. Two between-subjects (identification with a character acting as victimizer or victim) experiments address disparaging humorous advertising effectiveness, providing a novel perspective on very old questions. Perceived superiority and inferiority autonomously mediate the relationship between a disparaging advertisement and perceived humorousness. Individuals with high superiority motivation (i.e., high-katagelasticists) experience increased humorousness and an improved attitude toward the brand when they identify with a character acting as victimizer in the disparaging ad. People with a motivation to avoid inferiority (i.e., high-gelotophobes) experience reduced humorousness and lower positive attitudes toward the brand when they identify with a character who is victimized in the disparaging ad. Gelotophiles are not driven by feelings of superiority or inferiority and experience increased humorousness as well as more positive brand attitudes irrespective of the ad's victimization focus.
Keywords: Attitude Toward the Ad; Marketing; Advertisers